The Well-Being Of Female Headed Households In Rural And Urban Areas : A Case Study In North-Western Malaysia - Ghazali, Suriati; Atang, Colonius; Yaakob, Usman; Mohamed, Noriah; Jaafar, Jas Laile Suzana (USM, 2006)
Past research have indicated that households headed by women are usually poor compared to their male counterparts. This is due to insufficient sources and lack of land, skill or education which can help ensure a good life.